Tumor Targeting in Cancer Therapy - Pagé, Michel (New Jersey : Humana Press Inc., 2002)
In Tumor Targeting in Cancer Therapy, Dr. Michel Page and a panel of authoritative experts from the drug industry, clinics, and academia introduce the principles and techniques of tumor targeting and critically survey their applications from laboratory to bedside. By concisely synthesizing the many technical details, the authors illuminate this innovative technique, ranging from the fundamentals of drug targeting and in vivo and in vitro experimentation, to such emerging therapeutic uses as radioimmunotherapy, radio immunodetection, therapy with cytotoxic antibodies, immunotoxins, enzyme prodrug immunotherapy, and immunotherapeutics with fusion proteins. There are also reviews of targeting tumors with radioimmunoconjugates, photodynamic therapy, and magnetic drugs, as well as discussions of the internalization of antibodies, bioconjugation and biodistribution, the use of cytotoxic drugs, and the pros and cons of targeting by antibody or ligand.